Pelatihan Pembuatan Lele Kering dan Pemasaran Daring pada Sektor Agrobisnis Perikanan di Tengah Pandemi Covid-19 (Studi Kasus di Kelurahan Bugih, Kabupaten Pamekasan) - Putri Noviana T.; Masyithah Mardhatillah (PERDIKAN (Journal of Community Engagement), 2021)
This article observes training on producing dried catfish and seeling them online among catfish business owners at Bugih Village, Pamekasan Regency. Catfish cultivation in the area has been running so good that it is also processed into the dried catfish. Catfish cultivation and its processed products can be highly potential goods to sell amid the community's economic difficulties due to the COVID-19 pandemic. Catfish, which has been so far known only as fish eaten with rice in a meal, can be further processed such as becoming dried fish. The dried fish can increase public interest due to its durability. Those who don’t eat catfish in any common way can also be interested to taste the dried one. However, its market target is still limited to Pamekasan local area so that PKM (Pengabdian Kepada Masyarakat) participants in the area initiated to train the catfish sellers to dry the catfish and use online selling to enlarge potential customers and selling. We use SWOT analysis to capture the community service agenda after explaining the program quite detail. It reveals that catfish businessmen in the area are interested in processing dried catfish due to easy making process and economic potential of the product. They are also enthusiast to use online marketing wishing that it can increase income and help them dealing with economic difficulties during Covid-19 pandemic. (Artikel ini menyoroti pelatihan pembuatan lele kering dan pemasaran daring di kalangan para pebisnis lele di Kelurahan Bugih, Kabupaten Pamekasan. Budidaya lele di Kelurahan Bugih Kabupaten Pamekasan berjalan cukup baik, bahkan ada yang sudah membuat lele kering. Budidaya lele dan olahan produknya sangatlah potensial untuk dijual di tengah kesulitan ekonomi karena pandemi Covid-19. Lele yang selama ini hanya dikenal sebagai lauk yang biasa dimakan bersama nasi dapat dikembangkan menjadi produk olahan seperti ikan kering. Lele kering berpotensi meningkatkan minat beli masyarakat karena sifatnya yang tahan lama. Mereka yang tidak mau mengonsumsi lele seperti biasa juga mungkin tertarik mencicipi lele kering. Akan tetapi, pemasaran lele kering ini masih terbatas di wilayah lokal Pamekasan saja sehingga peserta PKM daerah setempat berinisiatif mengadakan pelatihan pembuatan lele kering dan pemasarannya secara daring untuk menambah pembeli potensial dan jumlah penjualan. Kami menggunakan anailsis SWOT untuk memotret pengabdian masyarakat tersebut setelah menjelaskannya cukup detail).